Assessment of a clinical score for screening suspected pulmonary tuberculosis cases - Castro, Cristiano Bel Alves de; Costa, Paulo Albuquerque da; Ruffino-Netto, Antonio; Maciel, Ethel Leonor Noia; Kritski, Afranio Lineu (Revista de Saúde Pública, 2011)
OBJECTIVE: To assess the accuracy (sensitivity) of a clinical score for presumptive pulmonary tuberculosis cases during screening. METHODS: Descriptive cross-sectional study comprising 1,365 patients attending the department of lung diseases at a secondary care outpatient clinic in the city of Rio de Janeiro, Southeastern Brazil, during 2006 and 2007. All respondents answered a standardized questionnaire administered by the clinic's nursing staff. Information on age, weight and clinical symptoms were collected. The presumptive diagnosis of pulmonary tuberculosis was made by summing up the scores of the data collected. The diagnosis of active tuberculosis was based on bacteriological findings and medical criteria. There were estimated sensitivity, specificity, positive predictive value and negative predictive value for a set prevalence, and 95% confidence intervals for different score cutoffs. The score performance was assessed using the receiver operating characteristic (ROC) curve. RESULTS: For the diagnosis of tuberculosis, cough for more than one week and cough for more than three weeks showed a sensitivity of 88.2% (86.2, 90.2) and 61.1% (57.93, 64.3), specificity 19.2% (16.6, 21.8) and 51.3% (48.1, 54.5), respectively. The clinical score of 8 had a sensitivity of 83.13% (77.8, 87.6), specificity of 51.8% (48.5, 55.1), positive predictive value of 91.6% (90.0, 83.2) and negative predictive value of 32.9% (30.1, 35.7). CONCLUSIONS: Cough for more than three weeks showed low sensitivity and specificity. A highly sensitive clinical score can be an alternative tool for screening pulmonary tuberculosis as it allows early care of suspected cases and standard nursing care approach.